Ecomorphological determinations in the absence of living analogs: the predatory behavior of the marsupial lion (Thylacoleo carnifex) as revealed by elbow joint morphology. - Figueirido-Castillo, Francisco Borja; Martín-Serra, Alberto; Janis, Christine Marie (Cambridge University Press, 2016)
Thylacoleo carnifex, or the “pouched lion” (Mammalia: Marsupialia: Diprotodontia: Thylacoleonidae), was a carnivorous marsupial that inhabited Australia during the Pleistocene. Although today all researchers agree that Thylacoleo had a hypercarnivorous diet, the way in which it killed its prey remains uncertain. Here we use geometric morphometrics to capture the shape of the elbow joint (i.e., the anterior articular surface of the distal humerus) in a wide sample of extant mammals of known behavior to determine how elbow anatomy reflects forearm use. We then employ this information to investigate the predatory behavior of Thylacoleo. A Principal Components Analysis indicates that Thylacoleo is the only carnivorous mammal to cluster with extant taxa that have an extreme degree of forearm maneuverability, such as primates and arboreal xenarthrans (pilosans). A Canonical Variates Analysis confirms that Thylacoleo had forearm maneuverability intermediate between wombats (terrestrial) and arboreal mammals, and a much greater degree of maneuverability than any living carnivoran placental. A Linear Discriminant Analysis computed to separate the elbow morphology of arboreal mammals from terrestrial ones shows that Thylacoleo was primarily terrestrial but with some climbing abilities. We infer from our results that Thylacoleo used its forelimbs for grasping or manipulating prey to much higher degree than its supposed extant placental counterpart, the African lion (Panthera leo). The use of the large and retractable claw on the semi-opposable thumb of Thylacoleo for potentially slashing and disemboweling prey is discussed in the light of this new information.
https://www.cambridge.org/core/services/open-research/green-open-access-policy-for-journals
Keywords: Paleontología; Animales depredadores; Carnívoros fósiles; Marsupiales fósiles; Artículaciones - Evolución; Codos - Evolución; Elbow joint; Predatory behaviour; Carnivoran; Marsupial